2018
DOI: 10.12965/jer.36292.146
|View full text |Cite
|
Sign up to set email alerts
|

Duration of wrist immobilization is associated with shoulder pain in patients with after wrist immobilization: an observational study

Abstract: The main goal of this study was to determinate the extent of the relationship between shoulder pain and time of wrist and thumb immobilization required after injury. One hundred twenty-three consecutive subjects presenting to the practice of different Orthopedic Specialist hospitals with a diagnosis of distal radius or scaphoid fracture that required wrist and thumb immobilization were screened for eligibility criteria. Upper extremity pain and the need for shoulder rehabilitation were assessed using the visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Adams et al [37] demonstrated that, in young healthy subjects, limited wrist motion inevitably led to a statistically significant worsening of their ratings in activities of daily living (DASH, PRWE), and limited or completely restricted wrist motion with or without pain is subsequently accompanied by impaired power and performance both in elbow and shoulder [6,38]. In patients sustained TWF, the lowest scores found were for perineal hygiene, using a screwdriver, and trouble using the hand in tight spaces such as changing spark plugs on the family car, followed by writing, drinking from a glass, turning a doorknob, combing hair, and using a hammer (i.e.…”
Section: What Is Evident When Wrist Motion Is Impaired?mentioning
confidence: 99%
“…Adams et al [37] demonstrated that, in young healthy subjects, limited wrist motion inevitably led to a statistically significant worsening of their ratings in activities of daily living (DASH, PRWE), and limited or completely restricted wrist motion with or without pain is subsequently accompanied by impaired power and performance both in elbow and shoulder [6,38]. In patients sustained TWF, the lowest scores found were for perineal hygiene, using a screwdriver, and trouble using the hand in tight spaces such as changing spark plugs on the family car, followed by writing, drinking from a glass, turning a doorknob, combing hair, and using a hammer (i.e.…”
Section: What Is Evident When Wrist Motion Is Impaired?mentioning
confidence: 99%
“…Limited or complete wrist or distal radioulnar joint (DRUJ) motion with or without pain is subsequently followed by impaired power and performance both in elbow and shoulder [16,22,23]. This pattern can be compensated by increased activities of trunk and shoulder muscles (upper trapezius and deltoideus) or using the other unaffected hand or both hands more often but over a not clearly known time [24][25][26].…”
Section: Introductionmentioning
confidence: 99%